Scalp Nerve Block In Reconstructive Craniotomy: A Case Report - Milhiandana Mitresna Salsabila; H. Andi Husni Tanra; Muhammad Wirawan Harahap (International Medical Journal Corp. Ltd, 2025)
Scalp block is an option in head surgery with certain procedures, namely when patient awareness is required, or techniques that require patient functional assessment and craniotomy. This block is performed on the supra orbital nerve, supra trochlea, zygomaticum temporal, auriculo temporal, auricular major, greater occipital and lesser occipital. We report a case of a 55-year-old man with Mild Traumatic Brain Injury GCS 14 + fracture of the Os Frontalis Sinistra, anterior wall of the Sinus Maxillaris dextra et sinisra and Os Zygomaticum sinistra, simultaneously for reconstructive craniotomy with scalp block anesthesia technique for post-surgical pain management. During the operation, hemodynamics were stable without complications. Post-surgery the patient was moved to the recovery room without complaints.